Productivity of rice (Oryza sativa) as influenced by crop diversification in wheat (Triticum aestivum) - rice cropping system on Mollisols of foothils of Himalayas * - SINGH, V K; SHARMA, B B (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during 1996-97 and 1997-98 on clay-loam soil at Pantnagar to identify the appropriate crop sequence for higher productivity of rainy season rice (Oryza sativa L.). The productivity of rice was measured in 10 crop sequences, viz wheat (Triticum aestivum L. emend. Fiori and Paol.) - rice, chickpea (Cicer arietinum L.) - rice, lentil (Lens culinaris L.) - rice, pea (Pisum sativum L.) - rice, wheat-mung bean (Phaseolus radiatus L.) green manure-rice, wheat-sesbania (Sesbania aculeata L.) green manure-rice, wheat-maize (Zea mays L.) +cowpea (Vigna unguiculata (L walp.) fodder - rice, chickpea - maize+cowpea fodder- rice, lentil- maize+cowpea fodder - rice and pea - maize+cowpea fodder - rice, Compared with wheat-rice sequence the productivity of rice was significantly higher under wheat-mung bean (green manure)-rice and wheat-sesbania (green manure)-rice sequences during both the years. On an average green manuring withmung bean or sesbania resulted in 18.39 and 13.64% increase in rice grain yield than under wheat-rice sequence (5.50 tonnes/ha). Growth parameters, viz plant height and dry-matter accumulation/hill and yield attributes, viz number of productive shoots, panicle length, number of fertile spikelets/panicle, grain weight/panicle and 1 000-grain weight were significantly higher under green manuring sequences. Among other sequences chickpea-rice proved superior to wheat-rice with respect to yield and growth parameters.